2022
DOI: 10.4314/ejhs.v32i4.23
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in the Sickle Cell Disease and Fetomaternal Outcomes in Different Sickle cell Genotypes: A Systematic Review and Meta- Analysis

Abstract: BACKGROUND: Pregnancy is a major concern among women with the sickle cell disease (SCD), and it is associated with increased adverse outcomes. The aim of the present meta-analysis is to report the fetomaternal outcomes in different sickle cell genotypes.METHODS: In this systematic review and meta-analysis, a comprehensive search of databases and search engines such as PubMed, Scopus, Web of Science, ProQuest, Cochrane Library, Science Direct and Google Scholar were performed. Any observational studies that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It is a well-known fact that pregnant women with SCD have a greater risk to develop maternal and fetal complications during pregnancy compared with healthy women [4][5][6][7][8]. In developing countries like those in Africa, a mortality rate of 7-12% persists [20,21] and in India it is 4-40% [22][23][24] as a result of SCD in pregnancy, because of poor and insufficient antenatal care especially in remote areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a well-known fact that pregnant women with SCD have a greater risk to develop maternal and fetal complications during pregnancy compared with healthy women [4][5][6][7][8]. In developing countries like those in Africa, a mortality rate of 7-12% persists [20,21] and in India it is 4-40% [22][23][24] as a result of SCD in pregnancy, because of poor and insufficient antenatal care especially in remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…SCD occurs in individuals homozygous for the βS globin gene (SS) or heterozygous for the βS allele and different abnormal β globin gene alleles, such as βC (SC), Sβ0 thalassemia, or Sβ+ thalassemia [3]. Pregnant women with SCD are at greater risk of obstetrical complications and perinatal mortality as well as sicklerelated complications [4][5][6][7][8]. Complications in the mother as well the fetus include anemia, prepartum and postpartum painful crises, preeclampsia, eclampsia, pulmonary complications, preterm delivery along with other associated risks, and intrauterine growth restriction (IUGR) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy with sickle cell disease (SCD) can be hazardous because the prospective mother and the newborn are at increased risk of complications [ 1 ]. Pregnancy-related physiological changes, such as increased metabolic demand, increased blood viscosity, and hypercoagulability, are exacerbated in SCD patients, increasing the risk of complications, such as a vaso-occlusive crisis, acute chest syndrome, osteonecrosis, hepatic necrosis, leg ulcers, and thromboembolic events [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the other SCD variants, the most common is SC hemoglobinopathy (HbSC). Several studies have reported maternal and fetal complications in pregnant women with SCD: perinatal mortality, preterm labor, fetal growth restriction, preeclampsia, acute painful crises, and urinary and pulmonary infections [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%